2022
DOI: 10.3390/ijms23073846
|View full text |Cite
|
Sign up to set email alerts
|

Katanin-Dependent Microtubule Ordering in Association with ABA Is Important for Root Hydrotropism

Abstract: Root hydrotropism refers to root directional growth toward soil moisture. Cortical microtubule arrays are essential for determining the growth axis of the elongating cells in plants. However, the role of microtubule reorganization in root hydrotropism remains elusive. Here, we demonstrate that the well-ordered microtubule arrays and the microtubule-severing protein KATANIN (KTN) play important roles in regulating root hydrotropism in Arabidopsis. We found that the root hydrotropic bending of the ktn1 mutant wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…As a universal stress hormone, cellular ABA has been shown to mediate plants’ development [ 15 , 16 , 17 , 30 , 36 , 37 , 38 ]. ABA is synthesized and accumulated in roots and regulates primary root growth in A. thaliana in a concentration-dependent manner, which exogenously applied in low concentrations stimulates, while at high concentrations inhibits root growth [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a universal stress hormone, cellular ABA has been shown to mediate plants’ development [ 15 , 16 , 17 , 30 , 36 , 37 , 38 ]. ABA is synthesized and accumulated in roots and regulates primary root growth in A. thaliana in a concentration-dependent manner, which exogenously applied in low concentrations stimulates, while at high concentrations inhibits root growth [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The microtubule cytoskeleton is widely involved in many key processes in plant morphogenesis [ 28 , 40 ] and the response to adverse environments [ 21 , 22 , 23 , 30 ] for the dynamic features, hence microtubule cytoskeletons are believed to perceive signal transduction in plant stress response [ 30 , 41 , 42 , 43 ]. However, the crosstalk and underlying mechanism between microtubules and these signals are still insufficiently studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microtubule (MT) is a critical constituent of the cellular cytoskeleton, and research has increasingly demonstrated a close relationship between the establishment of cell morphology in plant cells and the cortical MT array and dynamics within the cell [21,22]. KTN1, which encodes a katanin p60 subunit, plays an important role in plant cell morphogenesis [12,[22][23][24][25]. Studies have shown that KTN1 and KTN80 form KTN1-KTN80 heterodimers, which was activated by BZR1-family transcription factors (BFTFs), thereby associated with BRs signaling pathway to precisely perform MT severing and properly regulate filament elongation in Arabidopsis [12,22].…”
Section: Introductionmentioning
confidence: 99%